Forensic Linguistic Exploration of the Use of Taboo Words in Everyday Communication - Carolina Sasabone; Jefriyanto Saud; Ishak Bagea; Achmad Hidir; Ahmad Munawir (RETORIKA: Jurnal Ilmu Bahasa, 2024)
In contemporary communication dynamics, the usage of taboo words has become a focal point, reflecting the intricacies of human interaction. This study employs a forensic linguistic approach to delve into this phenomenon, specifically aiming to elucidate the underlying linguistic dynamics shaping language use in daily interactions. The analysis process incorporates specific forensic linguistic techniques, including discourse analysis and linguistic methodologies, to investigate the role of taboo words as significant evidence in both legal and social contexts. Through a fusion of qualitative research methods, data comprising taboo words, phrases, and sentences are gathered from community discourse via participant observation methods. Researchers meticulously document discourse through various means such as recordings, notes, and interviews, subsequently transcribing and categorizing the collected data. The findings of the analysis reveal three societal taboos: fear, delicacy, and propriety. Furthermore, this research concludes with a statement highlighting the broader implications of the findings, emphasizing the importance of understanding language's role in shaping social reality not only in everyday interactions but also in forensic contexts. This contributes to a deeper understanding of linguistic dynamics and their relevance in both legal and social spheres